Frontier Investor : How to Prosper in the Next Emerging Markets. - Dimitrijevic, Marko (Columbia Business School publishing, 2016)
Frontier markets account for 15 percent of global GDP, yet global investors largely ignore them. Fueled by access to technology and information, these markets are emerging even faster than their predecessors, making them an essential component of a globally diversified portfolio. In Frontier Investor, Marko Dimitrijevic makes the case for their inclusion, arguing#x97;through a diverse set of case studies#x97;that it is possible if not wise to make informed investing decisions about these unfamiliar and undervalued markets. Markets that were considered exotic two decades ago#x97;China, India, South Africa,